Influence of insulin resistance on renal function in patients with abdominal obesity - Pertseva T.O.; Rokutova M.K. (Medičnì Perspektivi)
The purpose of the study - to assess the role of insulin resistance in the development of initial manifestations of renal disease in patients with abdominal obesity. Materials and methods – 61 patients (I group) young with obesity, I-III degree, without diabetes 1 or type 2 were examined. The structure of the control group included 12 patients who were considered to be relatively healthy (II group), 10 patients with newly diagnosed type 2 diabetes (III group) and 10 individuals with uncomplicated hypertension without abdominal obesity and diabetes. The effect of hyperinsulinemia and insulin resistance indices on renal function (glomerular filtration rate, urine protein, urine albumin, urine І2-microglobulin, and relations - urine albumin / creatinine urine, І2-microglobulin urine/urine creatine) was studied. Results and discussion. Main group of patients, group of patients with diabetes type 2 and uncomplicated hypertension is characterized by disturbances in the form of hyperinsulinemia and increased insulin resistance index. Statistical analysis showed significant relationships between indicators of fasting insulin, IR index and renal function in patients with abdominal obesity. Regression analysis confirmed the pattern between the level of insulin resistance and the main indicators of renal function (GFR, MAU, І2-microglobulinuria and increased ratio І2-microglobulin/urine creatinine). Conclusions. In patients with abdominal obesity disorders in the form of hyperinsulinemia and increased insulin resistance index of HOMA-IR>2,77 were revealed. Significant correlation connections between levels of fasting insulin, insulin resistance index and indicators of renal function were observed. In regression analysis predictive role of insulin resistance in the formation of renal dysfunction in patients with abdominal obesity was established. The necessity of studying the state of insulin resistance in patients with obesity-associated nephropathy for the selection of adequate pathogenetic therapy, prognosis of renal dysfunction and prevention of the development of related metabolic disorders.